INDUCTION HEATING OF NON-MAGNETIC SHEET METALS IN THE FIELD OF A FLAT CIRCULAR MULTITURN SOLENOID - Batygin, Y.; Gnatov, A.; Argun, Sch.; Sabokar, O.; Батыгин, Ю. В.; Гнатов, А. В.; Аргун, Щ. В.; Сабокарь, О. С.; Батигін, Ю. В. (Харьковский национальный автомобильно-дорожный университет, 2016)
The theoretical analysis of electromagnetic processes in the system for induction heating presented by a flat circular multiturn solenoid positioned above a plane of thin sheet non-magnetic metal has been conducted. The calculated dependences for the current induced in a metal sheet blank and ratio of transformation determined have been obtained. The maximal value of the transformation ratio with regard to spreading the eddy-currents over the whole area of the sheet metal has been determined.
ИНДУКЦИОННЫЙ НАГРЕВ НЕМАГНИТНЫХ ЛИСТОВЫХ МЕТАЛЛОВ В ОБЛАСТИ ПЛОСКОГО ЦИЛИНДРИЧЕСКОГО МНОГОВИТКОВОГО СОЛЕНОИДА
ИНДУКЦИОННЫЙ НАГРЕВ НЕМАГНИТНЫХ ЛИСТОВЫХ МЕТАЛЛОВ В ОБЛАСТИ ПЛОСКОГО ЦИЛИНДРИЧЕСКОГО МНОГОВИТКОВОГО СОЛЕНОИДА
Keywords: induction heating; the induction system; the induced current; eddy current; heating of metal; индукционный нагрев; индукторная система; индуцированный ток; вихревые токи; нагрев металла; індукційне нагрівання; індукторна система; індукований струм; вихрові струми; нагрівання металу; 621.318.4